How are diagenesis and reservoir quality linked to depositional facies? A deltaic succession, Edgeøya, Svalbard. (April 2018) - Haile, B.G.; Klausen, T.G.; Czarniecka, U.; Xi, K.; Jahren, J.; Hellevang, H.
Abstract: Middle to late Triassic strata exposed at Edgeøya, eastern Svalbard, represents an uplifted part of the northwestern corner of the Barents Sea. This interval is characterized by a predominantly mud-dominated deltaic depositional system where rocks with petroleum reservoir potential are expected both in delta front and channelized sandstone deposits. Recent drilling campaigns into time-equivalent rocks in the Barents Sea have however been disappointing, with porosity and permeability below expectation. This study improves the current understanding of reservoir potential within depositional systems of this kind by examining the link between different depositional facies, diagenesis and their impact on reservoir quality. Five depositional facies were mapped and correlated: channel, floodplain, shallow marine, prodelta and offshore. Our study suggests that diagenetic signatures that control the quality of reservoir rocks vary systematically with these depositional facies. Mechanical compaction was the main cause of porosity destruction in the channel, shallow marine and floodplain samples, while early carbonate cementation occludes the intergranular volume in the prodelta samples. Moreover, quartz cement reduced the porosity in the shallow marine depositional facies. The estimated maximum burial temperature of 124 °C indicates burial to several km depths. Depositional settings within a deltaic to shallow marine system do not exert a strong control on the abundance of chlorite, but it does impact whether the chlorite is pore filling or grain coating and porosity preserving. Efficient chlorite coating have aided in preserving porosities up to 32% in the very well/well sorted medium to fine grained sandstones deposited by fluvial dominated channels. Highlights: Diagenetic signatures that control reservoir quality vary systematically as a function of depositional facies. The channel depositional facies associated with well-developed chlorite coating have notably better reservoir quality. Distribution of diagenetic signatures, depositional facies and sediment composition are key to predict reservoir quality.